An unusual cardiac mass resolving with antitubercular treatment - Aniruddha Vyas; K Rajeshwari; Sumod Kurien; Vimal Mehta; Nagaraj Pandarikar; Sanjay Tyagi (Wolters Kluwer Medknow Publications, 2014)
We present an interesting case of a 2½-year-old child with Tetrology of Fallot with a large intracardiac mass in the left ventricle presenting with fever and bilateral stroke, that resolving with antitubercular therapy alone.